Industri Rumahan Kue Bawang Medan Rizka di Kelurahan Padang Besi Tahun 1999-2019 - Naldi, Hendra; Azizah, Nur Aqlia (Universitas Negeri Padang, 2024)
This study aims to see the development of the Onion Cake Home Industry in the Padang Besi area to find out how the form of social economic impact caused by this Medan Rizka onion cake home industry for the community around the Padang Besi area. Even though the Medan Rizka Onion Cake is still fairly traditional and is still marketed in the city of Padang and its surroundings, even though the making of this Rizka onion cake started as a family meal during Eid every year, and starting in 1999, it began to be developed.In this study the method used is the historical method through data collection or heuristics, criticism, interpretation, and writing. In obtaining primary or secondary data, the authors do it in two ways, namely library research and field studies. The result of this research is that the development of the field onion cake home industry is marked by starting to look for their respective market areas to market their field onion cake production. Little by little the rizka field onion cake, Padang Besi Village began to be known in the market because of the delicious taste it offered